IDH1 R132C and ERC2 L309I Mutations Contribute to the Development of Maffucci’s Syndrome - Cheng, Peng; Chen, Kun; Zhang, Shu; Mu, Ke-tao; Liang, Shuang; Zhang, Ying (Frontiers in Endocrinology, 2021)
Background: Maffucci’s syndrome is characterized by the coexistence of multiple enchondromas and soft-tissue hemangiomas. It has been clear that somatic mosaic isocitrate dehydrogenase type 1 (IDH1) or isocitrate dehydrogenase type 2 (IDH2) mutations are associated with Maffucci’s syndrome and Ollier disease, but the mechanisms underlying hemangiomas of the Maffucci’s syndrome is still obscure. This study aimed to determine the mechanism of hemangiomas in Maffucci’s syndrome. Methods: We received a 26-year-old female patient with typical Maffucci’s syndrome, and exome sequencing was conducted using DNA from her peripheral blood and enchondroma tissues. Somatic mutations were characterized by a comparative analysis of exome sequences and further confirmed by the sequencing of PCR products derived from original original blood and tissue samples. The mutations of an additional 69 patients with Ollier disease were further evaluated. The functional impacts of these somatic mutations on Maffucci's syndrome, especially the development of hemangiomas, were evaluated. Results: We reported a typical case of Maffucci's syndrome, which was confirmed by both imaging findings and pathology. Through exome sequencing of this patient‘s DNA samples, we identified an R132C mutation in the isocitrate dehydrogenase type 1 (IDH1) gene and an L309I mutation in the ELKS/RAB6-interacting/CAST family member 2 (ERC2) gene in this patient. Approximately 33.3% of the clones were positive for the IDH1 R132C mutation, and 19.0% of the clones were positive for the ECR2 L309I mutation. The IDH1 R132 mutation was detected in most of the patients with Ollier disease (51/69 patients), and the mean frequency of this mutation was 63.3% in total sequence readouts, but the ECR2 L309I mutation was absent in all of the patients with Ollier disease. In vitro experiments confirmed that the IDH1 R132C mutation promotes chondrocyte proliferation, and the ERC2 L309I mutation enhances angiogenesis. Conclusions: Our results suggest that ERC2 is a novel gene identified in Maffucci’s syndrome. The somatic L309I mutation of ERC2 contributes to the pathogenesis of hypervascularization to facilitate the development of hemangiomas in Maffucci’s syndrome. The combination of the IDH1 R132C and ERC2 L309I mutations contributes to the development of Maffucci’s syndrome.